A Functional Analysis on the Interspecies Interaction between Mouse LFA-1 and Human Intercellular Adhesion Molecule-1 at the Cell Level - Núñez, David; Comas, Laura; Lanuza, Pilar M.; Sánchez-Martinez, Diego; Pérez-Hernández, Marta; Catalán, Elena; Domingo, María Pilar; Velázquez-Campoy, Adrián; Pardo, Julián; Gálvez, Eva M. (Frontiers in Immunology, 2017)
The interaction between intercellular adhesion molecules (ICAM) and the integrin lymphocyte function-associated antigen-1 (LFA-1) is crucial for the regulation of several physiological and pathophysiological processes like cell mediated-elimination of tumour or virus infected cells, cancer metastasis or inflammatory and autoimmune processes. Using purified proteins it was reported a species restriction for the interaction of ICAM-1 and LFA-1, being mouse ICAM-1 able to interact with human LFA-1 but not human ICAM-1 with mouse LFA-1. However, in vivo results employing tumour cells transfected with human ICAM-1 suggest that functionally mouse LFA-1 can recognise human ICAM-1. In order to clarify the interspecies cross-reactivity of the ICAM-1/LFA-1 interaction, we have performed functional studies analyzing the ability of human soluble ICAM-1 and human/mouse LFA-1 derived peptides to inhibit cell aggregation and adhesion as well as cell-mediated cytotoxicity in both mouse and human systems. In parallel, the affinity of the interaction between mouse LFA-1 derived peptides and human ICAM-1 was determined by calorimetry assays. According to the results obtained it seems that human ICAM-1 is able to interact with mouse LFA-1 on intact cells, which should be taking into account when using humanized mice and xenograft models for the study of immune-related processes.